Scenarios of availability of water due to overexploitation of the aquifer in the basin of Laguna de Santiaguillo, Durango, Mexico - María de Lourdes Corral-Bermudez; Eduardo Sánchez-Ortiz; Dioselina Álvarez-Bernal; Martín Omar Gutiérrez-Montenegro; Erika Cassio-Madrazo (PeerJ, 2019)
Background The importance of water to life is unquestionable. Most of the fresh water we use for daily activities comes from the aquifers, which in many cases due to misuse are overexploited and at risk. This article studies the aquifer that appeared in Laguna de Santiaguillo basin; it should be noted that the most important economic activity in the basin is agriculture. Methods By analyzing vector and demographic information, using GIS and with some field trips, the impact and risk on the level of disposition in every micro-basin that forms the basin were determined. Results The different modeling scenarios demonstrate that the basin and sub-basins that conform Santiaguillo are overexploited. Discussion The volumes concessioned are of such magnitude that they generate a condition of vulnerability to the activities of the basin and sustain the overexploitation conditions of the aquifer.